Relativistic effect inducing drag on fast-moving dislocation in discrete system. (March 2020) - Kim, Soon; Kim, Hokun; Kang, Keonwook; Kim, Sung Youb
Abstract: Phonon scattering, a dominant source of drag, is one of key issues to understand the dynamic behaviors of a dislocation. In this paper, it is found that a relativistic effect causes additional drag that is not ignorable when the dislocation's speed is comparable to the transverse shear wave speed. By considering the emission of lattice waves from the dislocation core, we theoretically derive an equation of dislocation motion wherein the relativistic effect is well considered in the frame of phonon scattering. Consequently, the relativistic drag force is characterized by two dimensionless constants that are newly defined in this study. Given that these constants depend on structural and oscillation properties of the dislocation core, a discrete nature of the core is well-reflected. Then, the solution of the equation, or the dislocation's speed, is compared with the result obtained by molecular dynamics simulation. Furthermore, the developed equation can explain a level-off behavior at high dislocation's speed by quantifying the relativistic drag force. Thus we can broaden our understanding of dislocation dynamics to fast-moving dislocations. Highlights: Relativistic effect increases the energy dissipation around the dislocation core as its speed approaches the transverse shear wave speed. The relativistic effect stems from increase of kinetic energy of the dislocation and is manifested by a spontaneous oscillation of the dislocation core. We developed a theoretical model based on discrete lattice dynamics theory and proved that the relativistic effect can be quantified by two dimensionless group parameters that are newly defined in this study. Our derived theoretical model was supported by molecular dynamics simulation of the dislocations.